METHODOLOGICAL APPROACHES TO DEVELOPING DOCUMENT HANDLING COMPETENCIES FOR LIBRARIANS AND USERS - Ubaydullayeva Durdonakhan Ma’rufjon Daughter (Bright Mind Publishing, 2025)
This article explores modern methodological approaches to developing document handling competencies among librarians and library users. With the rapid advancement of information technologies and the digital transformation of libraries, the ability to work effectively with documents is becoming increasingly important. The article examines the concept of competence, essential skills required for document handling, and practical methods to improve these competencies. Emphasis is placed on training programs, modular teaching methods, information literacy courses, and the integration of digital tools.
Keywords: Librarian, user, competence, document handling, methodology, information culture, digital library.